Improving Customer Service Quality in MSMEs through the Use of ChatGPT - Agus Dedi Subagja; Abu Muna Almaududi Ausat; Ade Risna Sari; M. Indre Wanof; Suherlan Suherlan (Politeknik Ganesha Medan, 2023)
In the current era of digitalisation, technological developments are accelerating and changing the way humans communicate and interact, including in MSME businesses. This study aims to evaluate the effect of using ChatGPT in improving the quality of customer service in MSMEs. By using ChatGPT technology, it is expected that MSMEs can provide better and effective services to their customers. The focus of this research is qualitative. Methods for gathering information included paying close attention and taking detailed notes, with subsequent analysis including data reduction, visualisation, and conclusions. The results of this study concluded that the use of ChatGPT can help MSMEs in improving the quality of customer service and efficiency in operations. MSMEs need to pay attention to several important things in using this technology, such as customer context and situation, staff training, privacy and security of customer data, and constraints in the use of technology. In the long run, the use of ChatGPT can help MSMEs in gaining better insights into customer preferences and improving customer satisfaction.